INFLUENCE OF VIDEO GAMES ON THE ACQUISITION OF THE ENGLISH LANGUAGE - Rudis, Domas; Poštić, Svetozar (Verbum, 2018)
In the past decade or two, there has been an obvious increase in the number of school children proficient in English. One of the reasons is the number of English classes per week, but even more importantly, it is the influence of the media. Students are greatly exposed to video games. In this paper, a survey was conducted in order to find the connection between video-game playing and English proficiency. Ninety six students filled out the survey answering a range of question on the quantity and quality of their video game playing. The conclusion drawn was that video games have a profound impact on language learning. The areas of most benefit were vocabulary and pronunciation. As a form of highly desirable entertainment, video games provide a positive and motivating atmosphere, which is perfect for adopting a foreign language.